Connecting children's worlds: Creating a multilingual syncretic curriculum through partnership between complementary and mainstream schools. (September 2013) - Kenner, Charmian; Ruby, Mahera
Children from minority-language backgrounds have multiple sites of learning: home, community, mainstream school, and in some cases complementary school where they study their mother tongue after school or at weekends. However, due to the institutional constraints of an education system based on monolingual principles, mainstream teachers are often unaware of the contribution that complementary classes make to children's learning, or unsure of how to draw on their pupils' linguistic knowledge in the curriculum. Children's multilingual identities and their other worlds of learning therefore remain invisible in mainstream school. This paper describes an action research study with teachers from complementary and mainstream schools in East London, in which they jointly planned lessons around topics that were then taught in both settings. The complementary teachers brought a holistic perspective based in the linguistic and cultural knowledge of their communities, which enabled these resources to be brought into mainstream learning, thus creating a syncretic curriculum that led to an increase in agency of children and their families as well as teachers themselves. We argue that collaboration between complementary and mainstream teacher colleagues can play a crucial role in constructing a space for multilingual learning in a monolingualizing society.